Evaluation of membranes for mimicry of an alveolar-capillary barrier in microfluidic lung-on-a-chip devices. (2022) - Kadyrova, Adina; Kanabekova, Perizat; Martin, Alma; Begimbetova, Dinara; Kulsharova, Gulsim
Abstract: An alveolar basement membrane plays a crucial role in the organogenesis and functioning of the lungs at the alveoli level. To emulate the function of the basement membrane in microfluidic lung-on-chip devices various types of membranes (film membranes, electrospun membranes) can be used. In this study, first thin-film membranes made of regenerated cellulose, polydimethylsiloxane (PDMS), and composite PDMS-cellulose were developed and evaluated on cell viability. Different polycaprolactone (PCL)-based electrospun membranes were then developed and compared to PDMS to evaluate their mechanical properties, cytotoxicity, and hydrophobicity. Fabricated nanofibers (PA15, P20, and P20M) showed relatively good fibers with occasional beads. All the membranes as well as PDMS were found to be hydrophobic and to absorb small molecules. Among the membranes, PA15 had the least toxic effect on cells and was found to be more optimal for further integration and use in lung-on-a-chip device applications. The study results pave the way towards emulation of an alveoli-capillary barrier in microfluidic lung-on-a-chip devices in the future.